Intercultural bilingual education in Chile - Williams Ibarra Figueroa; Elia Calderón Leyton (Revista Brasileira de História da Educação, 2016)
This article is based on analysis of the actions of public bodies and institutions that are being created in Chile to meet demand in Intercultural Bilingual Education (IBE). The aim is to analyze the practical training of students in initial teacher training in intercultural basic education at the Catholic University of Temuco. In addition, reveal the working methods of collaborative field between family-school- community partnership in key initial identification and subsequent components and devices in the proper relationship of individuals, in order to establish criteria by biopsychosocial processes from the identity the Other and You as host in the plural diversity of human beings, with aim is to recommend  a public policy with an emphasis on multicultural values of each community, enriching the human condition and biopolitics regarding the integration from the educational training and the role that fits the state.